Polio Supplementary Immunization Activities During COVID-19 Pandemic : Experience from Penampang District, Sabah, Malaysia - Sam Froze, Jiee; Melvin Ebin, Bondi; MUHAMMAD EZMEER, EMIRAL; Anisah, Jantim (SAGE Publications Inc, 2021)
Background: Polio Supplementary Immunization Activities (SIAs) were carried out in the State of Sabah in response to the Vaccine Derived Poliovirus outbreak declared in December 2019. Prior to this, Malaysia had been polio-free over the past 27years. This paper reported on the successful implementation of SIAs in the district of Penampang, Sabah, adapting (vaccine administration) to the COVID-19 pandemic. Methods: A series of meticulous planning, healthcare staff training, advocacy, and community engagement activities were conducted by the Penampang District Health Office. Bivalent Oral Polio Vaccine (bOPV) and monovalent Oral Polio Vaccine were administered over the period of 1 year via these methods: house to house, drive-through, static, and mobile posts. The targeted group was 22 096 children aged 13 years and below. Results: Polio SIAs in Penampang managed to achieve more than 90% coverage for both bOPV and mOPV. The overall vaccine wastage was reported to be 1.63%. No major adverse reaction was reported. Conclusion: High vaccine uptake during Polio SIAs in Penampang was attributed to good inter-agency collaboration, community engagement, intensified health promotion activities, and drive-through vaccination campaign.